2019
DOI: 10.1007/s10570-019-02781-7
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-related changes in the nanostructure of woods studied with X-ray and neutron scattering

Abstract: Wood and other cellulosic materials are highly sensitive to changes in moisture content, which affects their use in most applications. We investigated the effects of moisture changes on the nanoscale structure of wood using X-ray and neutron scattering, complemented by dynamic vapor sorption. The studied set of samples included tension wood and normal hardwood as well as representatives of two softwood species. Their nanostructure was characterized in wet state before and after the first drying as well as at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 44 publications
9
36
2
Order By: Relevance
“…72 h could not restore the initial hygroscopicity in the never-dried state completely. This was in line with the observations by Penttilä et al (2020), who found that drying and re-soaking wood samples in liquid water resulted in lower moisture contents at ca. 89% RH compared to never-dried samples for different soft-and hardwood species.…”
Section: Sorption Isotherms and Hysteresissupporting
confidence: 93%
“…72 h could not restore the initial hygroscopicity in the never-dried state completely. This was in line with the observations by Penttilä et al (2020), who found that drying and re-soaking wood samples in liquid water resulted in lower moisture contents at ca. 89% RH compared to never-dried samples for different soft-and hardwood species.…”
Section: Sorption Isotherms and Hysteresissupporting
confidence: 93%
“…In this study, the WAXS (i.e., Scherrer) analysis gave larger values regarding the average cellulose crystallite widths than the SAXS analysis regarding the diameters of cylinders presenting the elementary cellulose microfibrils. A similar discrepancy has been detected also earlier (Jakob et al 1995;Leppänen et al 2009;Penttilä et al 2019Penttilä et al , 2020. The larger crystallite widths obtained by WAXS can be explained by the aggregation of the elementary cellulose microfibrils (Jarvis 2018).…”
Section: Comparison Between Waxs and Saxs Results Of The Cellulose MIsupporting
confidence: 77%
“…This would also explain the larger role of the Gaussian term because this term could arise from the scattering from the nanosized pores of the G-layer. This interpretation and the related observations are strengthened by the results of beech TW measured by SAXS and small-angle neutron scattering (SANS) by Penttilä et al (2020) and the results of poplar TW measured by SANS by Sawada et al (2018).…”
Section: Saxs Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The differences caused by PEG were less dramatic but still significant in birch wood, which was the only representative of hardwoods in this study. This might be related to the overall smaller wet-state interfibrillar distance reported for hardwoods based on SANS and SAXS data 22,28,34 . In general, the results support previous findings from pulp www.nature.com/scientificreports/ fibers 17 , according to which the PEG molecules mostly occupy the spaces between microfibril bundles, but are not able to penetrate into the polymeric matrix between the individual microfibrils.…”
Section: Sans Reveals the Microfibril Bundlesmentioning
confidence: 93%